Thermal, morpholine, and radiation stressor effects on the embryonic development of lake whitefish (Coregonus clupeaformis) and round whitefish (Prosopium cylindraceum) - Lim, Michael (My University, 2016)
Lake and round whitefish are cold-adapted freshwater species with similar life histories and spawning behaviours. There have been several studies on the embryonic development of both species (particularly for lake whitefish), most utilizing constant temperatures. However, temperatures fluctuate in the field due to natural (e.g. seasonal changes) and anthropogenic (e.g. water discharged from once-through cooling processes) effects. Releases from once-through cooling processes may contain low levels of chemicals (e.g. morpholine) and radiation (e.g. tritium). This thesis examined and compared the impacts of thermal, morpholine, and radiation stressors on lake and round whitefish embryogenesis. To examine the effects of fluctuating incubation temperatures, lake and round whitefish were reared at constant temperatures, with seasonal temperature declines/inclines, transient temperature spikes, or seasonal temperature changes combined with temperature spikes. Round whitefish embryos had significantly higher mortality when reared at 8°C compared to lake whitefish, and seasonal temperature changes impacted development rate, growth, and hatch dynamics for both species. Temperature spikes had relatively little effect on development. The effects on embryonic development of chronic morpholine and low-dose radiation exposures were examined in round whitefish to compare with existing data in lake whitefish. Round whitefish embryos were more impacted by morpholine than lake whitefish (larger effects on growth and mortality at relatively lower concentrations) and v less impacted by low-dose radiation (little effect on growth or hatch dynamics). Post hatch, round whitefish embryos reared at 8°C, with rapid seasonal inclines, or with 500 mg L-1 morpholine had elevated mortality. All irradiated embryos had decreased mortality post-hatch compared to non-irradiated embryos. Thus, embryonic exposure to all stressors examined appears to alter post-hatch survival. This thesis better defines the effects of fluctuating incubation temperatures, chronic morpholine, and chronic radiation exposures on the embryonic development of lake and round whitefish. It also suggests that embryonic incubation conditions are important beyond hatching.
Environmental stressor effects on whitefish embryogenesis
Keywords: Embryo development; Lake whitefish; Round whitefish; Fluctuating Temperatures; Morpholine; Low-dose irradiation